Endogenous life expectancy and R&D-based economic growth - Paul Tscheuschner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2021)
We propose an overlapping generations framework in which life expectancyis determined endogenously by governmental health investments. As a novelty, we are able to examine the feedback effects between life expectancy and R&D-driven economic growth for the transitional dynamics. We find that i) higher survival induces economic growth through higher savings and higherlabor force participation; ii) longevity-induced reductions in fertility hampereconomic development; iii) the positive life expectancy effects of larger savingsand higher labor force participation outweigh the negative effect of a reductionin fertility, and iv) there exists a growth-maximizing size of the health caresector that might lie beyond what is observed in most countries. Altogether, the results support a rather optimistic view on the relationship between lifeexpectancy and economic growth and contribute to the debate surroundingrising health shares and economic development.
urn:nbn:de:bsz:100-opus-18586
Keywords: I15; J11; J13; J17; O41; 330; long-run growth; horizontal innovation; increasing life expectancy; welfare effects of changing longevity; size of health-care sectors